Changes in preference - Hansson, Sven Ove (Theory and decision, 1995)
A basic framework for studies of changes in preference is introduced, and four types of changes in preference are identified. Revision by a sentence such as 'A is better than B' means that a preference for A over B is acquired. The result of contraction b